Contemporary Dilemmas of Polish Foreign Policy Towards the Middle East. The case of Iraq and Qatar - Rafał Ożarowski (Siyasal: Journal of Political Sciences)
Poland is historically connected with the Middle Eastern states, and based on this fact in its foreign policy, it has regularly declared to achieve variable aims in the Middle East. Currently there are two kinds of interest which might be considered important in Polish foreign policy towards selected states of the Middle East. The first type is related to economic sphere when Poland tries to diversify gas and oil supplies, exemplified in agreements signed with Qatar. The second type refers to political interests, exemplified by the engagement of Poland in mission of stabilization in Iraq. The aim of this paper is to show the real capabilities of Polish foreign policy in the Middle East and identify the key obstacles to reach many aims. The author will also try to answer whether Polish foreign policy in the Middle East is effective or not and what reasons are behind that. The short-term perspective for the foreign policy of Poland towards the two Middle Eastern states of Qatar and Iraq will also be outlined.